2020
DOI: 10.1101/2020.09.08.285007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain volumetric changes in the general population following the COVID-19 outbreak and lockdown

Abstract: The COVID-19 outbreak introduced unprecedented health-risks, as well as pressure on the financial, social, and psychological well-being due to the response to the outbreak1–4. Here, we examined the manifestations of the COVID-19 outbreak on the brain structure in the healthy population, following the initial phase of the pandemic in Israel. We pre-registered our hypothesis that the intense experience of the outbreak potentially induced stress-related brain modifications5–8. Volumetric changes in n = 50 partici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…This is re ected in the reported results of the whole-brain analyses that demonstrated effects in regions that are not directly involved in emotional processing. However, our whole-brain ndings still largely overlap with the regional pro le reported by Salomon et al 12 demonstrating (besides previously mentioned amygdalar changes) volumetric increases in putamen and the anterior temporal cortex, which the authors linked to the intense experience associated with the COVID19 pandemic.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is re ected in the reported results of the whole-brain analyses that demonstrated effects in regions that are not directly involved in emotional processing. However, our whole-brain ndings still largely overlap with the regional pro le reported by Salomon et al 12 demonstrating (besides previously mentioned amygdalar changes) volumetric increases in putamen and the anterior temporal cortex, which the authors linked to the intense experience associated with the COVID19 pandemic.…”
Section: Discussionsupporting
confidence: 86%
“…For example, one study has demonstrated how a single extreme aversive global event may impact fear circuits by linking individuals' geographical proximity to the site of 9/11 terrorist attacks to the reactivation of the amygdala during memory recollection 11 . Similarly, a recent study also suggests that intense experience of the COVID19 outbreak is associated with a volumetric increase of the amygdala 12 .…”
Section: Introductionmentioning
confidence: 75%
“…Thus, market downs were associated with increased amygdala volume. This result is in line with the effect of a single extreme aversive global event on amygdala fMRI response 12 and with the COVID19 pandemic experience on amygdala volume 13 . Together these results show that effects of global events are profound enough to affect threat- and fear circuits on a population level.…”
Section: Main Textsupporting
confidence: 83%
“…For example, one study has previously demonstrated how a single extreme aversive global event may impact fear circuits by linking individuals’ geographical proximity to the site of 9/11 terrorist attacks to the reactivation of the amygdala during memory recollection 11 . Similarly, an upcoming study also suggests that intense experience of the COVID19 outbreak is associated with a volumetric increase of the amygdala 12 .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation